Calculation of radiation burden of personnel and public, working and living in area of the uranium mining and uranium-processing enterprises - Aumalikova, M; Ibrayeva, D; Zhumadilov, K; Shishkina, E; Bakhtin, M; Kashkinbayev, Ye (BULLETIN OF THE L.N. GUMILYOV EURASIAN NATIONAL UNIVERSITY. PHYSICS. ASTRONOMY SERIES, 2022)
The ionizing radiation throughout all time acted as the main external factor in evolutionary process. Today in many regions owing to radioactive pollution the general background appeared under the influence of technogenic sources of the ionizing radiation. Not only workers of the uranium industry, as well as the public of regions living near places of production and processing of uranium ore can be subject to threat of influence of small doses of radiation. Long-living radionuclides of technogenic origin make the main contribution to formation of a dose of external and internal radiation.